2013
DOI: 10.1073/pnas.1315828110
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 1 inhibits inflammatory helper T-cell development through controlling the innate immune response

Abstract: Programmed cell death 1 (PD-1) is an inhibitory coreceptor on immune cells and is essential for self-tolerance because mice genetically lacking PD-1 (PD-1 −/− ) develop spontaneous autoimmune diseases. PD-1 −/− mice are also susceptible to severe experimental autoimmune encephalomyelitis (EAE), characterized by a massive production of effector/memory T cells against myelin autoantigen, the mechanism of which is not fully understood. We found that an increased primary response of PD-1 −/− mice to heat-killed my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…In turn, infiltration of the brain and spinal cord by autoreactive CD4 T cells with the highest MOG affinity was unleashed in PD-1 deficient mice after MOG administration in complete Freund’s adjuvant (Figures 1B and S2). This necessity for PD-1 in dampening the activation of high affinity self-reactive CD4 T cells likely explains why the severity and incidence of EAE are both sharply exacerbated in the absence of PD-1 (Figure 1C) (Rui et al, 2013; Salama et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, infiltration of the brain and spinal cord by autoreactive CD4 T cells with the highest MOG affinity was unleashed in PD-1 deficient mice after MOG administration in complete Freund’s adjuvant (Figures 1B and S2). This necessity for PD-1 in dampening the activation of high affinity self-reactive CD4 T cells likely explains why the severity and incidence of EAE are both sharply exacerbated in the absence of PD-1 (Figure 1C) (Rui et al, 2013; Salama et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…Human polymorphisms that diminish PD-1 activity similarly increase the risk of autoimmune disorders such as systemic lupus erythematosus and multiple sclerosis (Kroner et al, 2005; Prokunina et al, 2002). In turn, mice deficient in PD-1 are also more susceptible to developing a variety of autoimmune disorders including dilated cardiomyopathy, neuronal demyelination, diabetes, arthritis and glomerulonephritis (Nishimura et al, 1999; Nishimura et al, 2001; Rui et al, 2013; Wang et al, 2005). Given this critical role for PD-1 in protection against autoimmunity in humans and rodent disease models, we sought to further investigate how this co-inhibitory molecule controls the activation and peripheral accumulation of autoreactive T cells.…”
Section: Introductionmentioning
confidence: 99%
“…The immune inhibitory function of PD-1 was demonstrated in PD-1 and PD-L1 knock-out mice, which presented hyperactive immune phenotypes (4, 7, 8), and mutations in PD-1 have been associated with disease progression in multiple human autoimmune disorders (911). High levels of PD-1 were linked to CD8 T cell exhaustion during chronic viral infections (5, 6, 1218).…”
Section: Introductionmentioning
confidence: 99%
“…Further supporting IL-17 signaling as a resistance mechanism to PD-1 blockade, Rui and colleagues found that an increased response of PD-1 knockout mice to heat-killed mycobacteria resulted in enhanced production of Th17 cells [194]. A causal relationship between PD-1 signaling and IL-17 response is suggested by the fact that tuberculosis patients were found to have increased numbers of PD-1+ T-cells compared with healthy individuals, and in this case, CD4+ T-cells secreted less IL-17 [195].…”
Section: Rationale For Combined Anti-pd1 and Anti-il-23/il-17 Treatmentmentioning
confidence: 95%